A Digital Baron for a Digital Age: Chris Hughes and Neoliberalism's Ascendancy in Journalism. Issue 6 (3rd July 2019) - Rooney, Shannon; Creech, Brian
Abstract: This article examines news media coverage surrounding Facebook co-founder Chris Hughes's purchase of the magazine The New Republic in March 2012 in order to reveal the ways in which media narratives situated him as a new kind of media owner for a new kind of media age. This textual analysis is embedded within the framework of metajournalistic discourse, aiming to interrogate the extent to which characterizations of Hughes are aligned with emerging digital practices and neoliberal ideals. This article pays particular attention to coverage in the immediate aftermath of his purchase as well as to the new owner's letter to readers and subscribers, ultimately arguing that Hughes is constructed as a self-enterprising and digitally savvy media owner, uniquely situated to preserve journalism by bringing tech industry philosophies and practices into the field. An abiding conflict between market logics and journalistic norms underscores the broader danger in knitting together neoliberal ideals of entrepreneurialism and startup culture with notions of how journalists can and should respond to financial and cultural threats of digital innovation to their industry.